"Marshall Lecture 2020: The Measure of Monopsony". Issue 6 (10th September 2021) - Langella, Monica; Manning, Alan
Abstract: There has been increasing interest in recent years in monopsony in the labour market. This paper discusses how we can measure monopsony power by combining insights from models based on both frictions and idiosyncrasies. It presents some evidence from the United Kingdom and the United States about how monopsony power varies across the wage distribution within markets, over the business cycle and over time.